Comparison of IgA Endomysium Antibody and IgA Tissue Transglutaminase Antibody in Celiac Disease - Helen R Gillett; Hugh J Freeman (Canadian Journal of Gastroenterology)
The antigen for immunoglobulin (Ig)Aendomysium antibody (EmA), a sensitive and specific serological marker for celiac disease, has recently been described as tissue transglutaminase (tTG). The aim of this study was to compare the assays used to measure IgAEmAand IgA tTG antibody in patients with celiac disease and disease control subjects. Sera from 21 patients with untreated celiac disease, 48 patients with treated celiac disease and 128 disease control subjects were tested both for IgA EmA with the use of indirect immunofluorescence against human umbilical cord and for IgA tTG antibody with the use of ELISA. Titres of IgA tTG antibody were significantly higher in both the untreated and treated celiac groups than in the disease control group. Titres in the treated group were, however, significantly lower than in the untreated group. A reference range was calculated to include 99.8% of the disease control group in whom small bowel biopsy showed no evidence of celiac disease. One patient from the disease control group with raised IgA tTG antibody titres and positive IgA EmA was found to have celiac disease on small bowel biopsy. The sensitivity, specificity, and positive and negative predictive values of the IgA EmA assay were all 100%. The sensitivity of the IgA tTG antibody assay was 95%, specificity 100%, positive predictive value 100% and negative predictive value 97.7%. An ELISA used to measure IgA tTG antibody is an excellent tool to screen for celiac disease and may prove useful for monitoring response to treatment.